2022
DOI: 10.12688/f1000research.74779.1
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift in medical education due to the COVID-19 pandemic: guidelines for developing a blended learning curriculum in medical education

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has transformed the world’s economy, health and education in a blink of an eye. Almost 1 billion learners have been affected across the globe. This has resulted in a paradigm shift to blended learning. Therefore, it was felt necessary to provide practical guidelines for the development of blended curriculum in medical education. It would help to overcome the challenges faced due to unprecedented transformation of medical education on account of pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
2
0
0
Order By: Relevance
“…Participants in this study inevitably linked psychological well-being and emotional experiences to the online teaching and learning platform. In line with the findings in this study, multiple authors have reported on the positive and negative experiences with online and blended learning since the COVID-19 pandemic (Connolly & Abdalla 2022 :1; Gordon et al 2020 :1; Rafi et al 2022 :1; Saber et al 2022 :1). This has resulted in the publication of, among others, guidelines for developing blended curricula in medical education (Rafi et al 2022 :1), best practice examples of moving healthcare education from traditional face-to-face teaching to blended learning (Tuthill, et al 2022 :1–11), and the dissemination of research on the challenges and barriers of blended learning in healthcare education (Saber, et al 2022 :8).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants in this study inevitably linked psychological well-being and emotional experiences to the online teaching and learning platform. In line with the findings in this study, multiple authors have reported on the positive and negative experiences with online and blended learning since the COVID-19 pandemic (Connolly & Abdalla 2022 :1; Gordon et al 2020 :1; Rafi et al 2022 :1; Saber et al 2022 :1). This has resulted in the publication of, among others, guidelines for developing blended curricula in medical education (Rafi et al 2022 :1), best practice examples of moving healthcare education from traditional face-to-face teaching to blended learning (Tuthill, et al 2022 :1–11), and the dissemination of research on the challenges and barriers of blended learning in healthcare education (Saber, et al 2022 :8).…”
Section: Discussionsupporting
confidence: 89%
“…In line with the findings in this study, multiple authors have reported on the positive and negative experiences with online and blended learning since the COVID-19 pandemic (Connolly & Abdalla 2022 :1; Gordon et al 2020 :1; Rafi et al 2022 :1; Saber et al 2022 :1). This has resulted in the publication of, among others, guidelines for developing blended curricula in medical education (Rafi et al 2022 :1), best practice examples of moving healthcare education from traditional face-to-face teaching to blended learning (Tuthill, et al 2022 :1–11), and the dissemination of research on the challenges and barriers of blended learning in healthcare education (Saber, et al 2022 :8). From the university where this study was conducted, limited documentation on online and blended learning has been published, even though several blended learning practices have continued beyond the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%